Classical Size Effects in Films of n-PbTe - M. A. Ruvinskii; O. B. Kostyuk; B. S. Dzundza (Фізика і хімія твердого тіла, 2015)
Based on kinetic Boltzmann equation the boundary problem of calculating the conductivity and Seebeck coefficient for a film with a rectangular cross section is solved. Mirror- diffuse mechanism of reflection of the charge carriers from the surfaces of the film is considered. Calculations were performed for different thicknesses nondegenerate semiconductor n-PbTe. A comparison of theoretical calculations with obtained experimental data for vapor-phase condensates based on PbTe is made. Keywords: classical size effects, thin film, lead telluride, thermoelectric properties.